Effectiveness of intervention training program on fire emergency response team knowledge and skill in selected vehicle service centres - Muhammad Shawal, Mohammad Sharif (2019)
Emergency response may be provided by a local government organization such as fire department, but an in-house Emergency Response Team (ERT) is the first responder to ensure the safety of the occupants. ERT training and response plans enable organization to respond timely in case of any emergency, however many firms are still unprepared. There is an effort by local authority, Fire and Rescue Department Malaysia to conduct the ERT training and execute the fire evacuation drill exercise. However there were no specific code of practice and guidelines have yet been developed on the ERT knowledge and skill requirement. The aim of this study was to develop a training module and gauge the effectiveness of intervention training program on ERT knowledge and skill. This was a quasi-experimental two group pre-post study to determine the effectiveness between before and after the intervention program. A total of 91 respondents were reported for each experimental and control group was selected from the ERT at thirteen vehicle service centers in Malaysia. Questionnaire was carried out to determine the socio-demographic. In addition to that, pre-posttest was conducted to gauge the knowledge on ERT roles and skill on command and control, rescue method and firefighting technique. ANCOVA was used to control the pretest scores and their differences in the group as the covariate. The results after the intervention shows there was a significant improvement of the ERT knowledge through training on their roles. While intervention through the practical training significantly improved the ERT skills in command and control, rescue method and firefighting technique. Finally the results shows that there was a significant improvement of the ERT knowledge and skill after the intervention program through the developed training module.